The naked sun - Asimov, Isaac, 1920-1992 (Asimov, Isaac, 1920-1992. Robot series, 2018)
On the planet of Solaria, Spacers live in almost complete isolation, tended by robot servants and disgusted by the thought of human contact. And yet, one of their number has been beaten to death. Incapable of solving the crime, the authorities of the Outer Worlds seek help from Earth, from renowned detective Elijah Baley. Partnered once again with the robot Daneel Olivaw, Baley travels to this strange new world and uncovers a plot that could change the relationship between humans and robots for ever.